Pengaruh Faktor Keperilakuan Organisasi Terhadap Implementasi Sistem Akuntansi Keuangan Daerah Pada Satuan Kerja Perangkat Daerah Kabupaten Bengkalis - Muhammad Fadhil Junery; Abdullah Aziz (LPPM ISNJ Bengkalis, 2018)
This study aims to determine how much influence superiors support, clarity of purpose and training on the implementation of regional financial accounting systems in the work unit of Bengkalis regency. The type of data from this study is quantitative descriptive using primary and secondary data. The data analysis technique used is multiple linear regression. The results of this study are the influence of organizational behavioural factors with a percentage value of 0.677 or 67.7% and the remaining 32.3% is influenced by other variables, namely the Regional Supervision Agency, internal control system, and organizational culture. This research is the latest research in Bengkalis Regency and can be a reference for further research.